Empowering Through Tradition: The Entrepreneurial Journey of Amirthalingam Kalasothy and Top Aarokiyam Industry - Priyanka, S.; Tharsika, K. (University of Jaffna, 2024)
Introduction: Amirthalingam Kalasothy, a woman entrepreneur and the founder of Top Aarokiyam Industry in Jaffna, is a traditional food artisan who has successfully built her business while challenging societal norms that often restrict women to domestic roles. Context and Challenges: During the civil war, Kalasothy's family fell into poverty, which led her to start a business centered on traditional natural food items. As a differently abled woman, sustaining the business proved to be very challenging. At that time, societal support, as well as financial and family assistance, were insufficient. Action Taken: She obtained loans from Samurthi Bank and other commercial banks, while the Department of Agriculture provided machinery to support her operations. The Association for the Rehabilitation of the Differently Abled also offered entrepreneurial assistance. Nowadays, her business strategies include utilizing social media platforms such as YouTube and Facebook to expand her reach. Achievements: The founder has effectively grown her business through social media, ensuring a stable life for her children. She now provides job opportunities for women, empowering them and contributing to her significant success. On International Women's Day, the Association for the Rehabilitation of the Differently Abled also honored her with a women entrepreneur award. She has been in business since 1998 and celebrated her silver jubilee in 2023. Future Aspiration: The founder plans to expand her business operations and install machinery to enhance productivity.
Keywords: Women entrepreneurship; Traditional food industry; Social media marketing; Financial assistance; Empowerment